2014
DOI: 10.1007/s40618-014-0217-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 17β-estradiol on the expression of dipeptidyl peptidase III and heme oxygenase 1 in liver of CBA/H mice

Abstract: Abstract:Background 17β-estradiol (E2) has well established cardioprotective, antioxidant and neuroprotective role and exerts a vast range of biological effects in both sexes. Dipeptidyl peptidase III (DPP III) is protease involved as activator in Keap1-Nrf2 signaling pathway, which is important in cellular defense to oxidative and electrophilic stress. It is generally accepted that oxidative stress is crucial in promoting liver diseases.Objective To examine the effect of E2 on the expression of DPP III and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Therefore, although nuclear localization signal of mouse DPP III cannot be predicted with high score, having in mind oxidation prone cysteinyl SH-groups in rodent DPP III and unconventional pattern of redox-sensitive NLSs [32] , we may consider the possibility that nuclear translocation of mouse DPP III could be regulated by the oxidation state of its cysteine residues. We have recently demonstrated that E 2 depletion in normoxic, physiological conditions caused the increase of endogenous oxidative stress, which can be abolished with E 2 administration [22] . Also, lower oxidative stress in E 2 -treated mice was in correlation with increased DPP III protein level, and upregulated Ho-1 gene and protein [22] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, although nuclear localization signal of mouse DPP III cannot be predicted with high score, having in mind oxidation prone cysteinyl SH-groups in rodent DPP III and unconventional pattern of redox-sensitive NLSs [32] , we may consider the possibility that nuclear translocation of mouse DPP III could be regulated by the oxidation state of its cysteine residues. We have recently demonstrated that E 2 depletion in normoxic, physiological conditions caused the increase of endogenous oxidative stress, which can be abolished with E 2 administration [22] . Also, lower oxidative stress in E 2 -treated mice was in correlation with increased DPP III protein level, and upregulated Ho-1 gene and protein [22] .…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that E 2 depletion in normoxic, physiological conditions caused the increase of endogenous oxidative stress, which can be abolished with E 2 administration [22] . Also, lower oxidative stress in E 2 -treated mice was in correlation with increased DPP III protein level, and upregulated Ho-1 gene and protein [22] . Moreover, it was reported earlier that significantly lower amount of DPP III protein was found in highly oxygenated rat tissue [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are reports showing its association with membranes, and most recently its nuclear localization was observed as well. [10] Extensive investigations of the biochemical properties, structure and dynamics of this protein have been conducted by our group. [11][12][13][14][15][16] An enhanced level of human DPP III activity and protein was found in endometrial carcinomas and in ovarian malignant neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using female animals have shown that 17-β-estradiol (E 2 ) can act as a mediator of higher glucose consumption [ 14 , 15 ]. In our previous studies we showed female-biased resistance to oxidative stress in young adult mice [ 16 ] that was in relationship with protective effect of E 2 [ 17 ]. Since most metabolic studies have been conducted in only one sex, little attention has been paid to understanding the sex specificity of the above mentioned molecular pathways [ 18 ].…”
Section: Introductionmentioning
confidence: 99%